Cardiometabolic risk factors among children who are affected by overweight, obesity and severe obesity - Nur Zati Iwani, Ahmad Kamil; Jalaludin, Muhammad Yazid; Roslan, Farah Aqilah; Mansor, Fazliana; Md Zain, Fuziah; Hong, Janet Yeow Hua; Zin, Ruziana Mona Wan Mohd; Yahya, Abqariyah; Ishak, Zahari; Selamat, Rusidah; Mokhtar, Abdul Halim (Frontiers in Public Health, 2023)
It is expected that the increasing severity of obesity exhibits more serious health effects. However, little is known about the prevalence and clinical characteristics of children who are affected by severe obesity in Malaysia. This study aims to investigate the prevalence of cardiometabolic risk factors and their association with obesity status among young children. This is a cross-sectional study using the baseline data obtained from the MyBFF@school intervention program involving school children who are affected by obesity. Obesity status was defined using the BMI z-score of the WHO growth chart. Cardiometabolic risk factors presented in this study included fasting plasma glucose (FPG), triglycerides, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), blood pressure, acanthosis nigricans, insulin resistance and metabolic syndrome (MetS). MetS was defined using the International Diabetes Federation 2007 criteria. The descriptive data was presented accordingly. The association between cardiometabolic risk factors, such as obesity status, and acanthosis nigricans with MetS were measured using multivariate logistic regression. Out of 924 children, 38.4% (n=355) were affected by overweight, 43.6% (n= 403) were affected by obesity and 18% (n=166) were affected by severe obesity. The overall mean age was 9.85±0.84 years old. The prevalence of hypertension, high FPG, hypertriglyceridemia, low HDL-C and the presence of acanthosis nigricans among children affected by severe obesity was 1.8%, 5.4%, 10.2%, 42.8% and 83.7%, respectively. The prevalence of children affected by obesity who were at risk of MetS (<10 years old) and MetS (>10 years old) was similar at 4.8%. Children affected by severe obesity had higher odds for high FPG (OR=3.27; 95%CI 1.12, 9.55), hypertriglyceridemia (OR=3.50; 95%CI 1.61, 7.64), low HDL-C (OR=2.65; 95%CI 1.77, 3.98), acanthosis nigricans (OR=13.49; 95%CI 8.26, 22.04), insulin resistance (OR=14.35; 95%CI 8.84, 23.30) and MetS (OR=14.03; 95%CI 3.97, 49.54) compared to children affected by overweight and obesity. The BMI z-score, waist circumference and percentage body fat showed a significant correlation with triglycerides, HDL-C, TG: HDL-C ratio, and HOMA-IR index. Children affected by severe obesity exhibit a higher prevalence and are more likely to develop cardiometabolic risk factors compared to children affected by overweight and obesity.